Disability, Health and Human Development - Mitra, Sophie (Palgrave Studies in Disability and International Development, 2018)
This open access book introduces the human development model to define disability and map its links with health and wellbeing, based on Sen's capability approach. The author uses panel survey data with internationally comparable questions on disability for Ethiopia, Malawi, Tanzania and Uganda. It presents evidence on the prevalence of disability and its strong and consistent association with multidimensional poverty, mortality, economic insecurity and deprivations in education, morbidity and employment. It shows that disability needs to be considered from multiple angles including aging, gender, health and poverty. Ultimately, this study makes a call for inclusion and prevention interventions as solutions to the deprivations associated with impairments and health conditions. .